Speech Prosody 2020 2020
DOI: 10.21437/speechprosody.2020-84
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic encoding of sarcasm at the sentence level in Dutch

Abstract: This study investigated the prosodic characteristics of sarcastic speech in Dutch. Twenty native speakers of Dutch produced sentences in a sarcastic and sincere way in a simulated telephone conversation task. Prosodic analysis at the sentencelevel shows that in Dutch sarcasm is characterised by a longer duration, lower intensity, and less vocal noise compared to sincere speech. Utterance type and speaker gender influence the use of pitch and duration to realise sarcasm: pitch is lowered in some utterance types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Past studies have revealed a strong relationship between a speaker’s f0 variation and the perceived attractiveness ( Xu et al, 2013 ), trustworthiness ( McAleer et al, 2014 ), sarcasm ( Jansen and Chen, 2020 ), and speakers’ intended stress ( Eriksson et al, 2013 ) at the lexical or the sentence level inferred from their voice. A further study found that a single word hello was enough for the listeners to distinguish speakers of different trustworthiness.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have revealed a strong relationship between a speaker’s f0 variation and the perceived attractiveness ( Xu et al, 2013 ), trustworthiness ( McAleer et al, 2014 ), sarcasm ( Jansen and Chen, 2020 ), and speakers’ intended stress ( Eriksson et al, 2013 ) at the lexical or the sentence level inferred from their voice. A further study found that a single word hello was enough for the listeners to distinguish speakers of different trustworthiness.…”
Section: Discussionmentioning
confidence: 99%